Impact of Campaigns of the Quezon City Police District Anti-Cybercrime Team Against Scams and Frauds - Bueno, Fitz Patrick (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study evaluated the impact of the Quezon City Police District Anti-Cybercrime Team’s campaigns against scams and fraud within the jurisdiction of Quezon City. Anchored on the conceptual link between social media awareness campaigns, public awareness, behavioral change, and cybercrime reduction, the study was further guided by Protection Motivation Theory and Empowerment Theory. A qualitative research design was used, supported by face-to-face interviews, documentary analysis, immersion, and thematic analysis. The respondents consisted of sixteen subjects identified from QCPD blotter records, including cases involving unjust vexation, cyber libel, online threats, middleman scams, Facebook hacking, identity theft, investment scams, vishing, phishing, text scams, online scams, recruitment scams, and employment scams. Findings revealed that cybercrime victimization was influenced by excessive social media use, limited digital literacy, blind trust in online information, age-related difficulty in using technology, and economic need. The QCPD Anti-Cybercrime Team’s programs, including hotlines, Facebook-based updates, barangay visits, seminars, information campaigns, digital forensic support, volunteers, and inter-agency collaboration, were perceived as helpful in improving awareness, reporting, and public confidence. Records also showed a nearly 34 percent decrease in cybercrime cases, from 159 to 105 incidents, with a high case-resolution rate. However, challenges remained, including limited awareness, weak digital literacy, resistance to change, insufficient infrastructure, delayed response, data privacy concerns, and the need for stronger cooperation. The study concluded that cybercrime may be prevented, reduced, and controlled through sustained awareness, institutional capacity, public trust, and community participation. The study supports SDG 4, SDG 9, SDG 11, SDG 16, and SDG 17 by promoting digital education, safer communities, stronger institutions, and collaborative cybercrime prevention. Its sustainability impact lies in strengthening institutional, governance, digital, and community-based responses to online scams and fraud.
Keywords: Anti-Cybercrime Campaigns; Community Engagement; Cybercrime Prevention; Digital Literacy; Quezon City Police District; Scams and Fraud; Social Media Awareness